2012
DOI: 10.1063/1.4745776
|View full text |Cite
|
Sign up to set email alerts
|

Magnetically active vacancy related defects in irradiated GaN layers

Abstract: We present the studies of magnetic properties of 2 MeV 4He+-irradiated GaN grown by metal-organic chemical-vapor deposition. Particle irradiation allowed controllable introduction of Ga-vacancy in the samples. The magnetic moments with concentrations changing between 4.3...8.3x10^17 cm^-3 showing superparamagnetic blocking at room temperature are observed. The appearance of clear hysteresis curve at T = 5 K with coercive field of about H_C = 270 Oe suggests that the formation of more complex Ga vacancy related… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…Comparing the obtained results with experiments, we note that, according to the results, the observed collective ferromagnetism in GaN systems [7][8][9][10][11] can originate from magnetic interaction between V Ga O N defects. And in Ga-rich InGaN alloys, we predict even stronger FM.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Comparing the obtained results with experiments, we note that, according to the results, the observed collective ferromagnetism in GaN systems [7][8][9][10][11] can originate from magnetic interaction between V Ga O N defects. And in Ga-rich InGaN alloys, we predict even stronger FM.…”
Section: Discussionsupporting
confidence: 67%
“…III-nitride materials such as GaN and InGaN have found their applications in advanced solid-state lighting technologies [1][2][3] and optoelectronic devices including diodes or solar cells [4][5][6]. Moreover, the ferromagnetism (FM) in GaN or InN without doping by transition metal atoms was recently observed [7][8][9][10][11]. This FM was ascribed to the formation of native defects, such as cation vacancies or their complexes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…5 Besides magnetically active complexes involving Ga vacancies in pristine GaN, 6 also GaN vacancies (V GaN ) in Mg and Er doped GaN and GaN vacancy complexes have been confirmed. 15,16 In this work, we will demonstrate long-range ferromagnetism induced by vacancy complexes in wurtzite GaN, incorporating both V Ga and V N , rather than the previously proposed V Ga induced ferromagnetism.…”
Section: Introductionmentioning
confidence: 92%
“…5,6 A special case is Gd-doped GaN, for which colossal magnetic moments have been reported. 3 Subsequent studies found the Gd atoms to behave paramagnetically and showed only weak indications of moment formation for the Ga atoms.…”
Section: Introductionmentioning
confidence: 99%